2018
DOI: 10.1093/tbm/ibx082
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a complex chronic care patient case conference on quality and utilization

Abstract: There is need for effective venues to allow teams to coordinate care for high-risk or high-need patients. In addition, health systems need to assess the impact of such approaches on outcomes related to chronic health conditions and patient utilization. We evaluate the clinical impact of a novel case conference involving colocated trainees and supervisors in an interprofessional academic primary care clinic. The study utilized a prospective cohort with control group. Intervention patients (N = 104) were matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Compared to the average US adult, HNHC patients spend more than twice as much on out‐of‐pocket expenses and nearly four times as much on overall health care services and medication, exceeding $21 000 for average annual per‐person spending 1,3 . Yet, interventions aimed to control costs and reduce unnecessary health care utilization in this population have proved largely ineffective, 4‐8 likely due to lack of consensus on the definition and characteristics of HNHC patients 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…Compared to the average US adult, HNHC patients spend more than twice as much on out‐of‐pocket expenses and nearly four times as much on overall health care services and medication, exceeding $21 000 for average annual per‐person spending 1,3 . Yet, interventions aimed to control costs and reduce unnecessary health care utilization in this population have proved largely ineffective, 4‐8 likely due to lack of consensus on the definition and characteristics of HNHC patients 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…However, on the patient level, only a few case conferences have taken place 26. A prospective matched cohort analysis of 208 patients could not demonstrate significant impacts of chronic care patient case conferences in primary care after 6 months 55. In addition, GPs reported the time to organise and coordinate these meetings as major barriers towards case conferences 56.…”
Section: Discussionmentioning
confidence: 94%
“…26 A prospective matched cohort analysis of 208 patients could not demonstrate significant impacts of chronic care patient case conferences in primary care after 6 months. 55 In addition, GPs reported the time to organise and coordinate these meetings as major barriers towards case conferences. 56 Nonetheless, the present results strongly support efforts to strengthen coordination of care within the outpatient sector and across different sectors on the patient level, in addition to general management conferences and disease-specific programmes.…”
Section: Discussionmentioning
confidence: 99%
“…To address this communication chasm, CBO respondents suggested that fundamental transformations in philosophy were necessary among both medical practitioners and policymakers in recognizing the importance of addressing the non-medical needs of older adults, and a will to devote resources accordingly. To achieve this critical paradigmatic shift, administrative efforts to routinize inter-organizational case conferences, and thus engender a collaborative mindset across entities (Reuther et al, 2012; Stott & Quinn, 2017; Weppner et al, 2018), could be especially valuable.…”
Section: Discussionmentioning
confidence: 99%